(3cJGH GdQhV GdaGjb aj GdehGYX hGdObGFbs - (3TYjH GdMQjajTs ((3eMeO Ydi WGgQ s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeg cJGH GdhQV GdaGjb ai GdehGYX hGdObGFb jTJed Ydi NWH hJfRjgGJ hCMGOjK eQhjGJ hbUGFO hMcGjGJ hObGFb habgjGJ hefGbH GdUGdMjf s
(3BNQgG (B:s
(3efgG GdNGeSI bGd jG QH Ef de JQMefi CfJ aef jQMefi HQMeJc jG ehSi Ch cGf jdjb HcQei Cf CQOg NGFHkG hbO Jcde HgPg GdcdeGJ aZaQJ dg hYahJ Yfg hCfG GdZahQ GdQMje Je GdMQajT HMSf Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B919s
Keywords: (3GdJUha hGdBOGH GdTQYjIs